Correlational study on the sense of humor and positive mental health in mental health professionals - Piñar-Rodríguez, Sergi; Rodríguez-Martín, Dolors; Corcoles-Martínez, David; Tolosa-Merlos, Diana; Leñero-Cirujano, Miriam; Puig-Llobet, Montse (Frontiers in Public Health, 2024)
Background: Mental health professionals require exceptional communication skills and the ability to maintain an empathetic and authentic attitude within the therapeutic relationship. It is crucial that they achieve an optimal balance of physical, mental, and social well-being to enhance their performance in this context. This necessity has sparked a growing interest in promoting mental health among these professionals by focusing on the evaluation of both Positive Mental Health and the Sense of Humour.Objective: To assess the level of sense of humour and positive mental health, and to analyse the relationships between the sense of humour construct, the positive mental health construct, and the sociodemographic, occupational, and educational characteristics of mental health professionals who care for patients in hospital and community settings.Methods: An observational, descriptive, and cross-sectional with a non-experimental quantitative approach study has been carried out. The study was conducted involving 130 mental health care professionals. Levels of sense of humour and positive mental health were evaluated using authenticated questionnaires, while the relationship between these two constructs and the sociodemographic, occupational, and training characteristics of health workers were analysed following STROBE guidelines.Results: The study involved 130 professionals, predominantly women (71.5%), with an average age of 41.4 years. The majority were nurses (45.4%) with varied work experience and educational levels. Regarding the PMHQ questionnaire, an average score of 102.6 was achieved in the general evaluation, showing an insignificant relationship with sociodemographic and occupational variables. However, a significant trend regarding age and autonomy was noted. On the other hand, the Multidimensional Sense of Humour Questionnaire produced an average score of 67.3, also without significant correlations with the variables under scrutiny. Although no positive relationships were found between the general scores of Positive Mental Health Questionnaire and Multidimensional Sense of Humour Questionnaire, a positive correlation emerged between the use of humour and situational control. In summary, the findings suggest that the level of autonomy and the use of humour may be associated with specific sociodemographic and occupational characteristics, although the precise relationship remains complex and requires further research.